Introducing English semantics - Kreidler, Charles W. (London Routledge, 2014)
Discusses the nature of human language and how linguists categorise and examine it. Covers meanings expressed in English words, prefixes, suffixes and sentences. Examines such relations as synonymy, antonymy, hyponymy, ambiguity, implication, factivity, aspect, and modality Draws comparisons between English and other languages Illustrates the importance of 'tone of voice' and 'body language' in face-to-face exchanges and the role of context in any communication.
Includes bibliographical references and index
Keywords: Cơ bản